2017
DOI: 10.1111/tmi.13004
|View full text |Cite
|
Sign up to set email alerts
|

Malaria exacerbates inflammation‐associated elevation in ferritin and soluble transferrin receptor with only modest effects on iron deficiency and iron deficiency anaemia among rural Zambian children

Abstract: Abstractobjective In 4-to 8-year-old Zambian children (n = 744), we evaluated the effects of adjusting for inflammation (a1-acid glycoprotein >1 g/l), with or without additional adjustment for malaria, on prevalence estimates of iron deficiency (ID) and iron deficiency anaemia (IDA) during low malaria (LowM) and high malaria (HighM) transmission seasons.methods To estimate adjustment factors, children were classified as: (i) reference (malaria negative without inflammation), (ii) inflammation without malaria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Thus, sTfR shows the amount of iron that is available for erythropoiesis and constitutes a biomarker of the functional iron compartment in the body [ 74 ]. The results of this study are in line with the findings reported in Zambia [ 56 ] and Tanzania [ 59 ], where malaria parasitemia was associated with a significant increase in plasma sTfR levels. In both studies, it was reported that malaria substantially increased sTfR concentrations, but with modest effects on ID and IDA, results which are consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, sTfR shows the amount of iron that is available for erythropoiesis and constitutes a biomarker of the functional iron compartment in the body [ 74 ]. The results of this study are in line with the findings reported in Zambia [ 56 ] and Tanzania [ 59 ], where malaria parasitemia was associated with a significant increase in plasma sTfR levels. In both studies, it was reported that malaria substantially increased sTfR concentrations, but with modest effects on ID and IDA, results which are consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Serum ferritin adjusted for inflammation using internal regression approach [ 54 ] was used to define the ID (depleted iron stores). Children were classified as having depleted iron stores if their SF concentration was < 15 μg/L [ 55 , 56 ]. Finally, sTfR levels of ≥ 8.3 mg/L were considered elevated and represented a FID in this populations [ 46 , 55 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…in populations where malaria is endemic when ferritin and sTfR have been used for estimating prevalence (53) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, COVID-19 infected patients have a higher proportion of laboratory alterations than those of co-infected individuals such as CRP, D-dimer, AST, and ALT. Nevertheless, thrombocytopenia, lymphopenia, mild anemia, elevated bilirubin, elevated D-dimer, and elevated ferritin were observed in Plasmodium monoinfected individuals [41][42][43][44]. Therefore, it is not clear whether laboratory parameters could be semi-diagnostic parameters for COVID-19 and Plasmodium co-infected individuals.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%